Makna Simbolik Prosesi Akkattang pada Masyarakat Makassar Berdasarkan Teori Semiotika Charles Sander Peirce - Husnul Khatimah; Hajrah Hajrah; Andi Fatimah Yunus (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. This study examines the symbolic meaning of a tradition and aims to describe the symbolic form and reveal the symbolic meaning contained in the Akkattang procession for the people of Makassar in Pallangga Village, Pallangga District, Gowa Regency. This study uses a qualitative descriptive research method using Charles Sanders Pierce's semiotic analysis. The data in this study are in the form of symbolic meanings contained in the symbols used in the Akkattang procession for the Makassar people in Pallangga Village, Pallangga District, Gowa Regency. The data sources in this study were the Akkattang procession and three sanro people who had deep knowledge of Akkattang. Data collection techniques used in this study were direct observation, interview techniques, and documentation techniques. The results of the research conducted by the researcher show that the symbolic forms contained in the Akkattang procession are: clean bathing (passili) contains a symbolic meaning of self-cleaning and rejecting reinforcements so that children avoid unwanted disasters during the procession, circumcision (akkattang) has a symbolic meaning as spiritual purification or converting a child, being carried (sompo) contains a symbolic meaning of having high knowledge and broad insight. While the equipment used during the Akkattang procession is: 1) Wok (pammaja'), 2) Water (je'ne), 3) Leaves (leko'), 4) Ladder (tuka'), 5) Rice (taste', 6) Candle (liling), 7) Brown sugar (golla eja), 8) Coconut (kaluku), 9) Pillow (paklungang), 10) Free-range chicken (jangang village), 11) Cotton (kapasa), 12) Small knife (lading caddi), 13) Silk sarong (lipa sabbe), 14) Bodo shirt, 15) Ring (cincing), 16) Cake (kanrejawa), 17) coins (doek racing). The symbolic meaning can be obtained a clear picture of meaning that the people of Makassar in Pallangga Village, Pallangga District, Gowa Regency interpret the symbolic forms in the Akkattang procession as symbols of hope, perseverance, prosperity so that it is hoped that in the future the child will be given protection and have a harmonious life that gives happiness in his life.Keywords: Symbolic meaning, Akkattang, Charles sanders pierce semiotics